Small Airway Dysfunction Measured by Impulse Oscillometry and Fractional Exhaled Nitric Oxide Is Associated With Asthma Control in Children - Lin, Liang-Mei; Chang, Yu-Jun; Yang, Kuender D.; Lin, Ching-Hsiung; Chien, Jien-Wen; Kao, Jun-Kai; Lee, Ming-Sheng; Chiang, Tsay-I; Lin, Ching-Yuang; Tsai, Yi-Giien (Frontiers in Pediatrics, 2022)
BACKGROUND: Impulse oscillometry (IOS) and fractional exhaled nitric oxide (FeNO) are sensitive, and non-invasive methods to measure airway resistance and inflammation, though there are limited population-based studies using IOS and FeNO to predict asthma control. OBJECTIVE: To investigate the utility of IOS and FeNO for assessing childhood asthma control in terms of small airway dysfunction and airway inflammation. METHODS: This prospective observational cohort study enrolled 5018 school children (6-12 years old), including 560 asthmatic children and 140 normal participants. FeNO, spirometry, IOS, bronchial dilation test, total IgE, and childhood asthma control test (C-ACT) were measured. FeNO, IOS, spirometry, and C-ACT results were correlated to childhood asthma with and without control. RESULTS: Uncontrolled asthmatic children had abnormal FeNO, IOS, and spirometric values compared to control subjects (P <0.05). IOS parameters with R5, R5-R20, X5, Ax, △R5, and FeNO can predict lower C-ACT scales by the areas under receiver operating characteristic curves (AUCs) (0.616, 0.625, 0.609, 0.622, 0.625, and 0.714). A combination of FeNO (>20 ppb) with IOS measure significantly increased the specificity for predicting uncontrolled asthma patients compared to FeNO alone (P < 0.01). A multiple regression model showed that small airway parameter (R5-R20) was the strongest risk factor [OR (95% CI): 87.26 (7.67-993.31)] for uncontrolled asthma patients. Poor control with lower C-ACT scales correlated with high FeNO (r = -0.394), R5 (r = -0.106) and R5-R20 (r = -0.129) in asthmatic children (P < 0.05). CONCLUSIONS: A combined use of FeNO and IOS measurements strongly predicts childhood asthma with or without control.